1986
DOI: 10.1128/iai.53.3.713-714.1986
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunization of hamsters against experimental infection with the Lyme disease spirochete

Abstract: Hamsters passively immunized with as little as 0.0125 ml of immune rabbit serum (indirect fluorescentantibody titer, 1:8,192) were protected from challenge with 1,000 50% infective doses of Borrelia burgdorferi. Cross-protection studies with Minnesota and Connecticut isolates of B. burgdorferi indicated no major differences in their capacity to elicit mutually protective antibodies in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
43
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 15 publications
8
43
0
Order By: Relevance
“…The primary immune defense mechanism against B. burgdorferi infection, as with other spirochetal infections, 23 is the specific humoral immune response. 24,25 The anti-B. burgdorferi antibody response in our stud- ies displayed characteristics seen previously.…”
Section: Discussionsupporting
confidence: 72%
“…The primary immune defense mechanism against B. burgdorferi infection, as with other spirochetal infections, 23 is the specific humoral immune response. 24,25 The anti-B. burgdorferi antibody response in our stud- ies displayed characteristics seen previously.…”
Section: Discussionsupporting
confidence: 72%
“…The manifestations of infection include characteristic skin lesions, erythema migrans (EM), a non-speci¢c £u-like illness, followed by neurological, cardiac or joint involvement [2^4]. Soon after the discovery of B. burgdorferi as an etiological agent of Lyme disease, vaccination of experimental animals with whole B. burgdorferi cells was found to provide protection against challenge and established an important role for antibody-mediated immunity in protection [5,6]. Further studies demonstrated that the induction of anti-bodies that killed B. burgdorferi speci¢cally was responsible for providing protection against infection [7^11].…”
Section: Introductionmentioning
confidence: 99%
“…In both NHPs and mice, the disease consists of chronic infection and inflammation. The arm of the immune system primarily responsible for spirochetal clearance is the humoral immune response,12, 13 and the infection in humans and animal models is dominated by B‐cell hyperactivity14 and the presence of plasma cells in tissue15–18 and cerebrospinal fluid 19–21…”
mentioning
confidence: 99%